2019
DOI: 10.5152/eurjrheum.2018.18114
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin level and rheumatoid arthritis disease activity

Abstract: Objective The present study aimed to determine the relationship between the serum hepcidin level and disease activity in patients with rheumatoid arthritis (RA). Methods This study was conducted on 80 patients with RA (36 cases with anemia of chronic disease [ACD] and 44 patients without ACD). Disease activity was measured by the 28-joint Disease Activity Score based on the erythrocyte sedimentation rate (DAS28-ESR). According to the DAS28-ESR score, 52 and 28 cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
1
5
0
7
Order By: Relevance
“…Functional iron deficiency in ACD can be due to overexpression of iron-regulatory hormone, hepcidin, leading to sequestration into storage sites from circulation, resulting in hypoferrinemia and iron-restricted erythropoiesis. Although decreased serum hepcidin levels were reported to correlate with the reduction of disease activity [52], this observation was not evident in other studies [53,54]. Hepcidin could be suppressed, independently of inflammation.…”
Section: Anemia Of Rheumatoid Arthritis (Ra)mentioning
confidence: 84%
“…Functional iron deficiency in ACD can be due to overexpression of iron-regulatory hormone, hepcidin, leading to sequestration into storage sites from circulation, resulting in hypoferrinemia and iron-restricted erythropoiesis. Although decreased serum hepcidin levels were reported to correlate with the reduction of disease activity [52], this observation was not evident in other studies [53,54]. Hepcidin could be suppressed, independently of inflammation.…”
Section: Anemia Of Rheumatoid Arthritis (Ra)mentioning
confidence: 84%
“…In one study, patients with RA and iron deficiency had significantly decreased serum hepcidin levels compared to those with RA and anemia with chronic inflammation 17 . As hepcidin is influenced by inflammation and iron metabolism, results differ on the influence on Hb and disease activity associated with hepcidin on RA 16,18 . Furthermore, in the same study of patients with RA, iron metabolism was related to serum hepcidin levels cross-sectionally, but inflammation was related longitudinally 19 .…”
Section: Discussionmentioning
confidence: 99%
“…12,24 Hepcidin median was highest in active RA and lowest in control subjects, with significantly different intermediate levels in inactive RA patients. In a study by Sahebari et al (2018), the authors found no relation between hepcidin levels and RA activity; they categorized RA activity using the 5.1 DAS28 cutoff limit. 25 Another study reported a significant increase of serum hepcidin with the active status (DAS28>3.2 was used to define disease activity).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sahebari et al (2018), the authors found no relation between hepcidin levels and RA activity; they categorized RA activity using the 5.1 DAS28 cutoff limit. 25 Another study reported a significant increase of serum hepcidin with the active status (DAS28>3.2 was used to define disease activity). 12 The results of the latter study are similar to our results.…”
Section: Discussionmentioning
confidence: 99%